O currículo em ação e a ação do currículo na formação do/a professor/a - Paraíso, Marlucy Alves (1995)
This dissertation analyses the curriculum in action of the curriculum concerning the teacher formation. The empiric research was centered on a High School Course – Emphasis on Teaching – and the analysis was based on the Curriculum Sociology. On this piece of work, the curriculum as privileged space of Power relations and as territory of cultural contestation is discussed. Thus, the explicit, occult and silence elements which are part of and which shape this curriculum are examined. The curriculum in action is analysed as offering and excluding opportunities to the students. On this process, the legitimation of the oficial knowledge on the parto f the students and teachers and the aspects of moral and control regulation registered in the investigated curriculum in action are discussed. Being sure that the silenced say much, the action of two silence fields of the formal curriculum of the Teaching Course is also analised: the struggle between cultures (countryside x city); and the gender relations in the teacher formation. These two themes are discussed with the argument that they are silence fields of the formal curriculum, but that they act in the curriculum in action, causing conflicts, dispute and redirecting the curriculum planned.